2013
DOI: 10.2175/193864713813692225
|View full text |Cite
|
Sign up to set email alerts
|

Determining Free Chlorine Residual CT Values to Meet California Title 22 Five-log Virus Inactivation Requirement

Abstract: The Sanitation Districts of Los Angeles County (Districts) have developed a two-step disinfection process called sequential chlorination. The process applies free chlorine and chloramines in sequence and effectively inactivates viral and bacterial target organisms while minimizing the formation of N-nitrosodimethylamine (NDMA) and trihalomethanes (THMs). To meet California Title 22 requirements as an alternative disinfection technology for "disinfected tertiary recycled water", the Districts embarked on this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
4
5
0
Order By: Relevance
“…This indicates that the MS2 inactivation was very rapid in the CTF MBR effluent and did not require a high NaOCl dose to meet the 5-log inactivation goal. This observation is consistent with the previous reports on bench-and pilot-scale free chlorine disinfection studies with MBR effluents (Hirani et al, 2014;Mansell et al, 2008;Mansell, et al, 2009), as well as those granular media-filtered tertiary effluents (Adelman et al, 2016;Huitric et al, 2013).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This indicates that the MS2 inactivation was very rapid in the CTF MBR effluent and did not require a high NaOCl dose to meet the 5-log inactivation goal. This observation is consistent with the previous reports on bench-and pilot-scale free chlorine disinfection studies with MBR effluents (Hirani et al, 2014;Mansell et al, 2008;Mansell, et al, 2009), as well as those granular media-filtered tertiary effluents (Adelman et al, 2016;Huitric et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…This also suggests that proper membrane cleaning to maintain the integrity of the MBR membranes is very important because impaired membranes would deteriorate the water quality and cause turbidity spikes, which could lead to Ct requirement to increase as demonstrated by the earlier works (Hirani et al, 2014;Mansell et al, 2008;Mansell et al, 2009). The minimum Ct value determined in this study was also comparable to the reported values for the free chlorine disinfection of granular media-filtered tertiary effluent in pilotand full-scale studies conducted to aim at the conditional approval of free chlorine disinfection at full-scale water reclamation facilities in California (Adelman et al, 2016;Huitric et al, 2013). The CTF became the first MBR-based water reclamation facility that received a conditional approval of free chlorine disinfection from the State Water Resources Control Board based on the result of this study.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations